(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2015)
The feminist always tries to restore the tarnished imageof the woman and glorify it. One evident trait among all the contemporary womenwriters in Indian writings in English is the revolutionary spirit with whichthey strive to write. Their writings are an explosion of suppressed desires andpent up feelings that have long been gathered. Women writers have proved thattheir writings are serious and require attention. They handle thingsefficiently balancing tradition and womanhood. To be a feminist is to be ableto create a specific feminine mode of writing, fighting for the liberation ofwomenfolk in subjugation and all those forces within and outside the societythat troubled the neat categories of the family and mutilated the feminine sideof a woman. The infiltration of the western culture gave a serious blow to theIndian traditional life and women who epitomes were upholding the family regimegradually became transformed into women in search of their sole identities andin search of a liberated independence.